An Analyiss of Pre-Service Teacher Education for Inclusion of Children With Hearing Impairment - Stackus Okwaput (The Center for Disability Studies and Services Brawijaya University, 2018)
Proponents of inclusion in special needs education argue that it is a human right for children with special needs to attain education with their ordinary peers. Underlying inclusion is the assumption thast teachers have the knowledge for addressing the diverse needs of learners in their classrooms. This study explored the provisions that might enable pre-service teacher trainees in Uganda to acquire knowledge for implementing inclusion for children with hearing impairment and the challenges that may hinder them from achieving that goal. The sample consisted of five teacher trainers and six teacher trainees. Data was collected using focus group discussions and interviews and analyzed following the thematic analysis procedures. The findings show that trainees might acquire knowledge for implementing inclusion from provisions made in the syllabus for special needs education and the college. Challenges in the teacher education system and negative attitudes may, however, hinder the achievement of this goal.